(untitled) (Medical Forum Monthly, 2023)
Objective: The present study aimed to assess the minimal invasive surgical modality or peripheral neurectomy for trigeminal neuralgia. Study Design: A retrospective study Place and Duration of Study: This study was conducted at the Department of Neurosurgery Jinnah Teaching Hospital, Peshawar from June 2022 to May 2023. Materials and Methods: All the patients underwent peripheral neurectomy were analyzed for complications, pain relief and recurrence, and additional procedure for treatment recurrence and follow-up were done for 36 months postoperatively. Results: The overall mean age was 52.6 ± 8.62 years (35-70 years). The preoperative mean VAS was 7.52± 0.9 (5.9-9). There was significant improvement in VAS during follow-up after two and three years that was 0.79 ± 1.34 and 1.5 ± 0.97 respectively. The condition most usually impacted the third division (inferior alveolar) in 12 cases (54.5%). The second division (infraorbital) affected 7 individuals (31.8%), while the first division (supraorbital) affected two patient (9.1%). The inferior alveolar neurectomies were performed under general anesthesia whereas other two procedures were done under local anesthesia. Intra-operative and postoperative complications were found insignificant. About 9.1% (n=2) patients had recurrent pain. Conclusion: Peripheral neurectomy gives effective pain relief for TN patients in the short to medium term. The technique significantly reduced the degree of preoperative anxiety, depression, and pain.